BUILDING ON THE MARS PLANET - Pershakov, Valeriy; Petrova, Tatyana (Proceedings of National Aviation University (archive), 2012)
The main task is the terraforming of the Mars planet. Nowadays it is a very important task, because there are a lot of problems on the planet Earth, which deals with the exhaustion of natural resources. The solution is in the colonizing and building on the Mars planet.